TJNPR 2019
DOI: 10.26538/tjnpr/v3i9.2
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Chemical Characterization of Extracts and Blended Mixture of Palm Oil Leaf

Abstract: Bearing in mind the need to explore the medicinal prospects of this agricultural waste, this study was aimed at the characterization of the chemical constituents of the different solvent extracts of the oil palm leaf. Materials and Methods Oil Palm Leaf and ChemicalsLeaves of Elaeis guineensis were collected from Ovwor Mixed Secondary School in Ughelli, Delta State, Nigeria in the month of May 11, 2016. The leaves were authenticated and identified at Forestry Research Institute of Nigeria, Ibadan with voucher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that organic solvents with varying polarities, including ethanol, n-butanol, acetone, ethyl acetate, n-hexane, and petroleum, effectively retain alkaloids. [62][63][64][65][66] As most alkaloids have medium polarity, 29 solvents like ethanol (used in the soxhlet method) and acidic ethyl acetate solution (used in the maceration B method) are ideal for extracting alkaloids, penetrating deeper and releasing more extractable compounds. This explains the higher yields obtained for soxhlet and maceration B methods, which may also explain the low values obtained by maceration A and refluxing methods, since a high polarity organic solvent as methanol was applied.…”
Section: Alkaloids Detectionmentioning
confidence: 99%
“…Previous studies have demonstrated that organic solvents with varying polarities, including ethanol, n-butanol, acetone, ethyl acetate, n-hexane, and petroleum, effectively retain alkaloids. [62][63][64][65][66] As most alkaloids have medium polarity, 29 solvents like ethanol (used in the soxhlet method) and acidic ethyl acetate solution (used in the maceration B method) are ideal for extracting alkaloids, penetrating deeper and releasing more extractable compounds. This explains the higher yields obtained for soxhlet and maceration B methods, which may also explain the low values obtained by maceration A and refluxing methods, since a high polarity organic solvent as methanol was applied.…”
Section: Alkaloids Detectionmentioning
confidence: 99%